Analytic Study in the “Sufi Comic Book 3” About the Concept of Self Purification in Islamic Education - Iftitahul Aini; Hariyanto Hariyanto (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
The objectives of this study are 1) Knowing the Tazkiyah An-Nafs concept in Islamic education, 2) Knowing the Tazkiyah An-Nafs concept in